Does Health Literacy of Hemodialyzed Patients Predict the Type of Their Vascular Access? A Cross-Sectional Study on Slovak Hemodialyzed Population - Zavacka, Martina; Skoumalova, Ivana; Geckova, Andrea Madarasova; Rosenberger, Jaroslav; Zavacky, Peter; Pobehova, Jana; Majernikova, Maria (International journal of environmental research and public health, 2020)
Effective vascular access (VA) is an essential condition for providing hemodialysis, affecting patients' health outcomes. We aim to explore how health literacy (HL) as a non-clinical factor is associated with the decision-making process regarding VA type selection. Using data from 20 dialysis centers across Slovakia (n = 542, mean age = 63.6, males = 60.7%), the association of HL with type of VA (arteriovenous fistula (AVF) vs. central venous catheter (CVC)) was analyzed using a logistic regression model adjusted for sociodemographic characteristics and comorbidity. Sociodemographic data and data on nine domains of HL were collected by questionnaire. Data on VA and comorbidity were obtained from a medical records. Patients with a greater ability to engage with healthcare providers (odds ratio (OR): 1.34; 95% confidence interval (CI): 1.00-1.78), those with a better ability to navigate the healthcare system (OR: 1.41; 95% CI: 1.08-1.85), those more able to find good health information (OR: 1.52; 95% CI: 1.15-2.03), and those who understand it well enough to know what to do (OR: 1.52; 95% CI: 1.12-2.06) are more likely to have AVF. Patients' HL is associated with the type of VA; therefore, it should be considered in the decision-making process regarding the selection of the type of VA, thereby informing strategies for improving patients' HL and doctor-patient communication.
Keywords: Surveys and Questionnaires; Kidney Failure, Chronic; Arteriovenous Fistula; logistické modely; Humans; lidé středního věku; Renal Dialysis; Decision Making; Female; Aged; arteriovenózní píštěl; rozhodování; dialýza ledvin; senioři; komorbidita; lidé; centrální žilní katétry; Central Venous Catheters; zdravotní gramotnost; Health Literacy; Slovenská republika; Slovakia; průzkumy a dotazníky; ženské pohlaví; chronické selhání ledvin; Male; Comorbidity; Middle Aged; Odds Ratio; Cross-Sectional Studies; mužské pohlaví; odds ratio; průřezové studie; Logistic Models